Identification and molecular docking of novel ACE inhibitory peptides from protein hydrolysates of shrimp waste. Issue 9 (15th July 2018) - Krichen, Fatma; Sila, Assaâd; Caron, Juliette; Kobbi, Sabrine; Nedjar, Naima; Miled, Nabil; Blecker, Christophe; Besbes, Souhail; Bougatef, Ali
Abstract: The effect of enzymatic hydrolysis by Savinase on the interfacial properties and antihypertensive activity of shrimp waste proteins was evaluated. The physicochemical characterization, interfacial tension, and surface characteristics of shrimp waste protein hydrolysates (SWPH) using different enzyme/substrate (E/S) (SWPH5 (SWPH using E/S = 5), SWPH15 (SWPH using E/S = 15), and SWPH40 (SWPH using E/S = 40)) were also studied. SWPH5, SWPH15, and SWPH40 had an isoelectric pH around 2.07, 2.17, and 2.54 respectively. SWPH5 exhibited the lowest interfacial tension (68.96 mN/m) followed by SWPH15 (69.36 mN/m) and SWPH40 (70.29 mN/m). The in vitro ACE inhibitory activity of shrimp waste protein hydrolysates showed that the most active hydrolysate was obtained using an enzyme/substrate of 15 U/mg (SWPH15 ). SWPH15 had a lower IC50 value (2.17 mg/mL) than that of SWPH5 and SWPH40 (3.65 and 5.7 mg/mL, respectively). This hydrolysate was then purified and characterized. Fraction F1 separated by Sephadex G25 column which presents the best ACE inhibition activity was then separated by reversed‐phase high performance liquid chromatography. Four ACE inhibitory peptides were identified and their molecular masses and amino acid sequences were determined using ESI–MS and ESI–MS/MS, respectively. The structures of the most potent peptides were SSSKAKKMP, HGEGGRSTHE, WLGHGGRPDHE, and WRMDIDGDIMISEQEAHQR. The structural modeling of anti‐ACE peptides from shrimp waste through docking simulations results showed that these peptides bound to ACE with high affinity.